Adding a late fall application of Proxy (ethephon) before two traditional spring applications improves seedhead control of annual bluegrass. Issue 1 (22nd May 2020) - Reicher, Zachary J.; Sousek, Matthew D.; Patton, Aaron J.; Van Dyke, Adam; Kreuser, William C.; Inguagiato, John C.; Miele, Kevin M.; Brewer, John; Askew, Shawn D.; Hathaway, Aaron; Nikolai, Thomas A.; Kowalewski, Alec; et al.
Abstract: Annual bluegrass (ABG) ( Poa annua L.) is a prolific seed producer in the spring on golf courses that in turn decreases aesthetic quality and trueness of ball roll on cool‐season putting greens. Proxy (ethephon) applied twice in the spring after green‐up is the current industry standard after the loss of Embark (mefluidide) from the turf and ornamental market. However, plant growth regulators including Proxy have been used for years to help suppress ABG seedheads with inconsistent success. The primary objective of this study was to determine if ABG seedhead suppression is improved by adding a late fall application of Proxy to the two traditional spring applications of plant growth regulators at nine locations with diverse environments. A second objective was to determine the importance of including Primo Maxx (trinexapac‐ethyl) in fall and spring applications. Adding a late fall application of Proxy prior to the two spring applications (F+S+S) improved control of ABG seedheads over the traditional two spring applications (S+S), but the magnitude of improvement varied among locations. When treatments were applied F+S+S, the industry standard tank mixture of Proxy + Primo Maxx provided consistent ABG seedhead control and turf quality, similar to Proxy + Fiata (phosphonate + proprietary pigment) and equal to or better than Proxy alone.